2016
DOI: 10.1021/acs.jpcc.5b11709
|View full text |Cite
|
Sign up to set email alerts
|

Band Gap Opening in Dual-Doped Monolayer Graphene

Abstract: By means of periodic density functional calculations, we have studied the effect of dual doping on the stability and electronic structure of graphene. To this end, we substituted two carbon atoms with one 2p element (B, N, or O) and one 3p element (Al, Si, P or S). We determined that, in all cases, dual doping is much easier to attain than the introduction of only one dopant into the graphene framework. We demonstrate that this conclusion does not depend on the chemical species used to compute the formation en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 76 publications
11
43
0
Order By: Relevance
“…We have included this section to show that our work is in line with the recent study by Denis et al 53 who showed that certain classes of dual doped graphene have tendency to be more stable and easier to synthesise than their corresponding mono-doped graphene. For example, they pointed out that Al-X (where X = B, N, O) dual doped graphene are more stable than Al-doped graphene, and as such they would be easier to synthesise.…”
Section: Formation Energies Of Bes Co-doped Graphenesupporting
confidence: 82%
See 1 more Smart Citation
“…We have included this section to show that our work is in line with the recent study by Denis et al 53 who showed that certain classes of dual doped graphene have tendency to be more stable and easier to synthesise than their corresponding mono-doped graphene. For example, they pointed out that Al-X (where X = B, N, O) dual doped graphene are more stable than Al-doped graphene, and as such they would be easier to synthesise.…”
Section: Formation Energies Of Bes Co-doped Graphenesupporting
confidence: 82%
“…Furthermore, we have calculated the difference between the formation energy (F.E) of Be-S co-doped and the sum of the formation energies of Be-doped and S-doped graphene to check if this study is in agreement with the recent study by Denis et al 53 who showed that the F.E of certain classes of dual doped graphene is less than the sum of the formation energies of the corresponding mono-doped graphene systems. To calculate the formation energy of co-doped and mono-doped graphene systems, we employed the following formula:…”
Section: Methodssupporting
confidence: 76%
“…This material has been synthesized recently and proved to be an excellent catalyst for hydrogen evolution reactions [34], as well as anode materials for Li batteries [35]. Undoubtly, the most investigated member of the family of dual doped systems is SN dual doped graphene [36][37][38][39][40][41][42][43][44]. As a result, there are several useful approaches to synthesize it.…”
Section: Introductionmentioning
confidence: 99%
“…In effect, we have studied monolayer graphene doped with two heteroatoms, one 2p and one 3p element [43,44]. We noted that the introduction of two dopants modifies the structure of graphene and hence its electronic, magnetic and catalytic properties too.…”
Section: Introductionmentioning
confidence: 99%
“…The most widespread of these are doping with nitrogen (N), boron (B) and oxygen (O). However, there are still other interesting heteroatoms to be explored such as sulphur (S) and phosphorus (P) [2][3][4][5][6]. Some studies have reported about the synthesis of CNTs doped with S and P grown from catalyst.…”
Section: Introductionmentioning
confidence: 99%